5‐amino‐2‐methylpyridinium hydrogen fumarate: An XRD and NMR crystallography analysis. (29th March 2020) - Corlett, Emily K.; Blade, Helen; Hughes, Leslie P.; Sidebottom, Philip J.; Walker, David; Walton, Richard I.; Brown, Steven P.
Abstract: Single‐crystal X‐ray diffraction structures of the 5‐amino‐2‐methylpyridinium hydrogen fumarate salt have been solved at 150 and 300 K (CCDC 1952142 and 1952143). A base–acid–base–acid ring is formed through pyridinium‐carboxylate and amine‐carboxylate hydrogen bonds that hold together chains formed from hydrogen‐bonded hydrogen fumarate ions. 1 H and 13 C chemical shifts as well as 14 N shifts that additionally depend on the quadrupolar interaction are determined by experimental magic angle spinning (MAS) solid‐state nuclear magnetic resonance (NMR) and gauge‐including projector‐augmented wave (GIPAW) calculation. Two‐dimensional homonuclear 1 H‐ 1 H double‐quantum (DQ) MAS and heteronuclear 1 H‐ 13 C and 14 N‐ 1 H spectra are presented. Only small differences of up to 0.1 and 0.6 ppm for 1 H and 13 C are observed between GIPAW calculations starting with the two structures solved at 150 and 300 K (after geometry optimisation of atomic positions, but not unit cell parameters). A comparison of GIPAW‐calculated 1 H chemical shifts for isolated molecules and the full crystal structures is indicative of hydrogen bonding strength. Abstract : Single‐crystal X‐ray diffraction structures of the 5‐amino‐2‐methylpyridinium hydrogen fumarate salt have been solved at 150 and 300 K (CCDC 1952142 and 1952143). 1 H and 13 C chemical shifts as well as 14 N shifts that additionally depend on the quadrupolar interaction are determined by experimental magic angle spinning (MAS) solid‐state nuclear magnetic resonance (NMR) and gauge‐including projector‐augmented wave (GIPAW) calculation. Two‐dimensional homonuclear 1 H‐ 1 H double‐quantum (DQ) MAS and heteronuclear 1 H‐ 13 C and 14 N‐ 1 H spectra are presented.